Extrinsic and intrinsic factors related to recovery process in people with schizophrenia - Fernandez, Aaron; Tan, Kit Aun; Masiran, Ruziana; Abdul Rahim, Riana (Hampstead Psychological Associates, 2019)
The objective of this study was to examine the associations between recovery processes, recovery-oriented practices, and symptom severity in people with schizophrenia attending clinics at Hopital Kuala Lumpur.